Coping with a life event in bipolar disorder: ambulatory measurement, signalling and early treatment - Knapen, Stefan E (BMJ Case Rep, 2016)
Disruption of the biological rhythm in patients with bipolar disorder is a known risk factor for a switch in mood. This case study describes how modern techniques using ambulatory assessment of sleep parameters can help in signalling a mood switch and start early treatment. We studied a 40-year-old woman with bipolar disorder experiencing a life event while wearing an actigraph to measure sleep-wake parameters. The night after the life event the woman had sleep later and shorter sleep duration. Adequate response of both the woman and the treating psychiatrist resulted in two normal nights with the use of 1 mg lorazepam, possibly preventing further mood disturbances. Ambulatory assessment of the biological rhythm can function as an add-on to regular signalling plans for prevention of episodes in patients with bipolar disorder. More research should be conducted to validate clinical applicability, proper protocols and to understand underlying mechanisms.